Effects of an auxiliary pump on the performance of TDFA - Abdul Rashid, Hairul Azhar; Abd Rahman, Faidz; Ahmad, Harith; Emami, Siamak Dawazdah; Harun, Sulaiman Wadi (SP MAIK Nauka/Interperiodica, 2008)
An efficient fluoride-based thulium-doped fiber amplifier (TDFA) is theoretically demonstrated using a dual pumping scheme. Differential equations are solved directly in the theoretical analysis. An auxiliary pump at 1560 nm is used for ground-state absorption to enhance the excited-state absorption provided by the main pump of 1050 nm and, thus, to improve the gain and noise figure of the TDFA. A gain improvement of more than 10 dB is obtained at the 1470-nm region with the use of a 1560-nm pump at 20 mW. A small signal gain as high as 30 dB is obtained at this region with 100 mW of a 1050-nm pump and 20 mW of a 1560-nm pump using a 20-m of thulium-doped fiber. The corresponding noise figure is obtained at lower than 5 dB.